Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Solve for [tex][tex]$x$[/tex][/tex] using the quadratic formula: [tex][tex]$x^2+4x+4=0$[/tex][/tex]

[tex]\[
x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}
\][/tex]

A. [tex][tex]$x=-2$[/tex][/tex]

B. [tex][tex]$x=-1$[/tex][/tex]

C. [tex][tex]$x=0$[/tex][/tex]

D. [tex][tex]$x=1$[/tex][/tex]


Sagot :

To solve the quadratic equation [tex]\(x^2 + 4x + 4 = 0\)[/tex] using the quadratic formula, we will follow a step-by-step approach.

The general form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex], where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are constants. For this specific equation, we can identify the coefficients as follows:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 4\)[/tex]
- [tex]\(c = 4\)[/tex]

The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

Now we'll apply these steps:

1. Calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the discriminant formula:
[tex]\[ \text{Discriminant} = 4^2 - 4(1)(4) \][/tex]
[tex]\[ \text{Discriminant} = 16 - 16 \][/tex]
[tex]\[ \text{Discriminant} = 0 \][/tex]

2. Evaluate the discriminant:
Since the discriminant is zero, it indicates that there is exactly one real root (a repeated root).

3. Apply the quadratic formula:
Since we have a discriminant of zero, the quadratic formula simplifies to:
[tex]\[ x = \frac{-b}{2a} \][/tex]
Substituting the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ x = \frac{-4}{2(1)} \][/tex]
[tex]\[ x = \frac{-4}{2} \][/tex]
[tex]\[ x = -2 \][/tex]

Thus, the solution to the quadratic equation [tex]\(x^2 + 4x + 4 = 0\)[/tex] is:
[tex]\[ x = -2 \][/tex]

None of the other provided options ([tex]\(x = -1\)[/tex], [tex]\(x = 0\)[/tex], [tex]\(x = 1\)[/tex]) are correct since we derived that the only solution is [tex]\(x = -2\)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.